Does an Early and Aggressive Combined Wrapping and Dangling Procedure Affect the Clinical Outcome of Lower Extremity Free Flaps?—A Randomized Controlled Prospective Study Using Microdialysis Monitoring - Neubert, Nils; Vogt, P. M.; May, M.; Boyce, M.; Koenneker, S.; Budde, E.; Jokuszies, A. (Journal of Reconstructive Microsurgery, 2016)
Background The ideal starting point for flap training (FT) with the combined wrapping and dangling procedure is still a question of debate. Most units follow their own established protocols and currently evidence of flap compromise due to FT is still lacking. The aim of this study was to prove if an early and “aggressive” wrapping and dangling protocol could lead to metabolic changes, measured by microdialysis, indicating ischemia resulting in compromised flap perfusion.Methods Between 2010 and 2014, 49 patients with microvascular free flap reconstruction of the lower limb were included in this study. Patients were randomized into two groups. Group I started FT on the 7th postoperative day, and group II started on day 3. FT consisted of a combined wrapping and dangling procedure doubling its duration daily and ending at day 5. Flaps were monitored clinically and by microdialysis for ischemia-induced changes and metabolic parameters in the flap tissue in respect to different starting points of FT.Results All 49 patients in both groups were able to complete the postoperative FT without complications. Noninferiority of the early group could be proven and microdialysis results showed no differences between both groups.Conclusion We could prove by microdialysis that an early start of FT does not lead to compromised flap perfusion. Moreover, an early start of FT can lead to a reduced length of hospital stay. Furthermore, a reduced risk for deep vein thrombosis, pulmonary embolism, and pneumonia due to earlier mobilization might be an appreciated side effect.
Keywords: microdialysis; free flaps; monitoring; wrapping; dangling